An oligomeric state‐dependent switch in the ER enzyme FICD regulates AMPylation and deAMPylation of BiP. (18th September 2019) - Perera, Luke A; Rato, Claudia; Yan, Yahui; Neidhardt, Lisa; McLaughlin, Stephen H; Read, Randy J; Preissler, Steffen; Ron, David
Abstract: AMPylation is an inactivating modification that alters the activity of the major endoplasmic reticulum (ER) chaperone BiP to match the burden of unfolded proteins. A single ER‐localised Fic protein, FICD (HYPE), catalyses both AMPylation and deAMPylation of BiP. However, the basis for the switch in FICD's activity is unknown. We report on the transition of FICD from a dimeric enzyme, that deAMPylates BiP, to a monomer with potent AMPylation activity. Mutations in the dimer interface, or of residues along an inhibitory pathway linking the dimer interface to the enzyme's active site, favour BiP AMPylation in vitro and in cells. Mechanistically, monomerisation relieves a repressive effect allosterically propagated from the dimer interface to the inhibitory Glu234, thereby permitting AMPylation‐competent binding of MgATP. Moreover, a reciprocal signal, propagated from the nucleotide‐binding site, provides a mechanism for coupling the oligomeric state and enzymatic activity of FICD to the energy status of the ER. Synopsis: Regulation of the endoplasmic reticulum chaperone BiP involves AMPylation and deAMPylation, both of which are catalysed by the ER protein FICD. This study shows how transitions in FICD's oligomeric state enable switching of the activity of this bifunctional enzyme. FICD forms high‐affinity dimers that exhibit BiP deAMPylation activity and repressed AMPylation activity. Monomerisation of FICD allosterically releases AMPylation‐autoinhibition, permitting AMPylation‐competent ATP binding, whilst reciprocally inhibiting FICD's deAMPylation activity. Changes in the ADP/ATP ratio influence FICD's monomer‐dimer equilibrium in vitro, suggesting a functional link between BiP modification and the energy state of the endoplasmic reticulum. Abstract : The bifunctional enzymatic activity of FICD in regulating AMPylation of the endoplasmic reticulum chaperone BiP is conferred by transitions of its oligomeric state.